MUSIKALISCHE ABDRÜCKE DER BESTREBUNG SKRJABINS NACH MYSTISCHER SELBSTVERWIRKLICHUNG - FEKETE, Miklós (Studia Universitatis Babes-Bolyai Musica, 2018)
Musical Reflections of Scriabins Aspiration for Mystical Self-Fulfillment. This paper focuses on the artistic innovations of the Russian composer Alexander Scriabin, and examines the religious-philosophical ideology which influenced his life, and which contributed to the novelty of his musical oeuvre. Numerous musical analysis proposed to investigate and to systemize the particularities of the composer’s innovative melodic and harmonic language. The study reflects on a few of the quite different analytical approaches, and summarizes through the opinion of the musicologist Zsolt Gárdonyi, which expands the romantic harmonic analysis with the investigation of new harmonic structures based on different scale-types, especially the Acoustic scale (and Acoustic tonality).